Soil-plant micronutrients dynamics in response to integrated fertilization under wheat–soybean cropping system at Rawalakot, Pakistan. Issue 5 (16th April 2018) - Khaliq, Abdul; Zafar, Mohsin; Abbasi, M. Kaleem; Hussain, Imtiaz
ABSTRACT: This study provided an insight on improving soil-plant micronutrients availability in response to poultry manure (PM), wheat milling residues (WMR) and urea N (UN) and their integration in wheat–soybean cropping system. The treatments were: control; poultry manure full, PM100 ; wheat milling residues full, WMR100 ; urea N full, UN100 ; PM half and WMR half, PM50 +WMR50 ; UN50 +PM50 ; UN50 +WMR50 ; UN50 +PM25 +WMR25 . All amendments were added at the rate or equivalent to 100 kg total N ha –1 . Results indicated that the integrated treatments increased Cu, Fe, Mn and Zn uptake of wheat by 35.7–103%, 48.4–111.1%, 85.2–267.0% and 33.8–128.2%, respectively over control. In soybean the corresponding increase in micronutrient uptake (Cu, Fe, Mn and Zn) was 18.3–60.3%, 27.5–87.4%, 14.1–54.6% and 13.2–58.0% in integrated treatments. The post-harvest soil analysis indicated 2 to 3-fold increase in micronutrient content with highest values in PM100 i.e., 2.66 mg kg −1 for Cu, 14.41 mg kg −1 for Fe, 18.58 mg kg −1 for Mn and 2.44 mg kg −1 for Zn, respectively. The results showed that the PM either alone or in integrated with WMR and UN can be an effective management strategy for improving micronutrient content of soil–plant.